2014
DOI: 10.1371/journal.pone.0098159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cationic Polyacrylamide Characteristics on Sewage Sludge Dewatering and Moisture Evaporation

Abstract: The effects of the molecular weight (MW) and charge density (CD) of cationic polyacrylamide (CPAM) on sludge dewatering and moisture evaporation were investigated in this study. Results indicated that in sludge conditioning, the optimum dosages were 10, 6, 6, 4, and 4 mg g−1 CPAM with 5 million MW and 20% CD, 5 million MW and 40% CD, 3 million MW and 40% CD, 8 million MW and 40% CD, and 5 million MW and 60% CD, respectively. The optimum dosage of CPAM was negatively correlated with its CD or MW if the CD or MW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
10
0
1
Order By: Relevance
“…Hereinto, the part of the dissolved organics was further oxidized to small molecular substances . The concentrations of protein and polysaccharide were used as an index to measure the degree of EPS degradation . The Fenton reaction system generated hydroxyl radicals (•OH) with the existence of H 2 O 2 and the catalysis of Fe 2+ under acidic conditions, and the amount of Fe 2+ and H 2 O 2 directly influenced the production of •OH .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hereinto, the part of the dissolved organics was further oxidized to small molecular substances . The concentrations of protein and polysaccharide were used as an index to measure the degree of EPS degradation . The Fenton reaction system generated hydroxyl radicals (•OH) with the existence of H 2 O 2 and the catalysis of Fe 2+ under acidic conditions, and the amount of Fe 2+ and H 2 O 2 directly influenced the production of •OH .…”
Section: Resultsmentioning
confidence: 99%
“…[29] The concentrations of protein and polysaccharide were used as an index to measure the degree of EPS degradation. [30][31] The Fenton reaction system generated hydroxyl radicals (•OH) with the existence of H 2 O 2 and the catalysis of Fe 2þ under acidic conditions, and the amount of Fe 2þ and H 2 O 2 directly influenced the production of •OH. [32][33] The generation of hydroxyl radicals (•OH) was deficient under low H 2 O 2 concentration, which inhibited the effect of sludge dewatering.…”
Section: Effect Of Fe 2þ and H 2 O 2 Dosages On Sludge Dewatering Usimentioning
confidence: 99%
“…Zhu et al [4] determined that the best sludge dewatering performance is obtained by CPAM with the highest MW. Zhou et al [9] indicated that the optimum dosage of CPAM is negatively correlated with its MW if the MW of CPAM reaches above five million. Thus, studies focusing on the preparation technology of CPAM constantly optimize MW synthesis conditions [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al determined that the best sludge dewatering performance is achieved by CPAM with the highest MW [4]. Zhou et al indicated that the optimum dosage of CPAM is negatively correlated with its MW if the MW of CPAM reaches above 5 million [9].…”
Section: Introductionmentioning
confidence: 99%